2006
DOI: 10.1007/s10565-006-0039-7
|View full text |Cite
|
Sign up to set email alerts
|

The effects of subchronic methidathion toxicity on rat liver: Role of antioxidant vitamins C and E

Abstract: Methidathion (MD) phosphorodithioic acid S-[(5-methoxy-2-oxo-1,3,4-thiadiazol-3(2H)-yl)methyl] O,O-dimethyl ester is the organophosphate insecticide (OPI) most commonly used worldwide in the pest control of crops. Subchronic MD exposure was evaluated for its effects on lipid peroxidation, the serum activities of cholinesterase (ChE), and enzymes concerning liver damage, and the protective effects of combination of vitamins E and C in albino rats. Additionally, the histopathological changes in liver tissue were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 18 publications
5
30
0
2
Order By: Relevance
“…These observations possibly come from the toxic effects of generated reactive oxygen species which upset the liver membrane components. Similarly, OP-treated rats have experienced almost the same perturbations including inflammation, and hepatocellular degeneration (Gokalp et al, 2003;Kalender et al, 2010;Sutcu et al, 2006). However, the co-treatment of Se plus Zn has reduced the histological alterations induced by MD, which might be attributed to their antiradical/antioxidant roles.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…These observations possibly come from the toxic effects of generated reactive oxygen species which upset the liver membrane components. Similarly, OP-treated rats have experienced almost the same perturbations including inflammation, and hepatocellular degeneration (Gokalp et al, 2003;Kalender et al, 2010;Sutcu et al, 2006). However, the co-treatment of Se plus Zn has reduced the histological alterations induced by MD, which might be attributed to their antiradical/antioxidant roles.…”
Section: Discussionmentioning
confidence: 96%
“…Only corn oil was given in the same way to the control group. The dose of MD used in this study represents 1/15 of LD50 (5 mg/kg bw) which has been used previously by other investigators since it is toxic but not lethal to rats (Sutcu et al, 2006;Güney et al, 2007). The doses of Na2SeO3 and ZnSO4 were selected based on the clinical application and on results from previous experiments in human and experimental animals against heavy pesticide poisoning (Goel et al, 2005;Mansour and Mossa, 2009;Ben Amara et al, 2011).…”
Section: Animals and Treatmentmentioning
confidence: 99%
“…Pesticide are hydrophobic molecules that bind widely to biological membranes, essentially phospholipid bilayers [27] , and they may cause damage to the membranes by generate lipid peroxidation. [26] Previous studies have reported that methidathion caused oxidative damage by lipid peroxidation in rat aortic wall, heart tissue, liver and ovary [28,12,8,15]. [29] have shown that single-dose treatment with methidathion increases lipid peroxidation in rat erythrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…[29] have shown that single-dose treatment with methidathion increases lipid peroxidation in rat erythrocytes. [8] have shown lipid peroxidation may be a molecular mechanism contributory in methidathion induced toxicity. lipid peroxidation occur through the generation of reactive oxygen species (ROS) that may be produced as a result of methidathion metabolism or due to high energy consumption to inhibit oxidative phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation